Deslocados ambientais e as hierarquias de reconhecimento: o Brasil na ordem migratória global - Perlingeiro, Mona Licia Santana (2025)
This dissertation aims to understand migration flows related to climate change by linking the lack of legal and political recognition of environmentally displaced persons to social structures rooted in colonialism and global capitalism. To this end, international treaties and agreements on climate governance were analyzed, highlighting the absence of recognition of human mobility driven by environmental factors. The investigation draws on critical theoretical foundations concerning racial hierarchies of life, seeking to reveal how the Global North’s response to migrants from the Global South — those most affected by climate change — has been shaped by restrictive and criminalizing migration policies. The research also examines the Brazilian context, marked by a migratory history shaped by exclusionary racial dynamics and institutional limitations in formulating public policies that recognize and protect people in situations of environmental displacement. In this regard, particular attention is given to the organization and resolutions of the National Conferences on Migration, Refuge and Statelessness (COMIGRAR), as well as to the emblematic case of the floods in Rio Grande do Sul in 2024, which led to the displacement of thousands of people and exposed significant gaps in institutional responses to environmental disasters and forced mobility.